Mathematical Modelling on Convective Boundary Layer of Non-Newtonian Micropolar Viscoelastic Fluid - L. A., Aziz; N. S., Arifin; S. M., Zokri; Abdul Rahman, Mohd Kasim; Mohd Zuki, Salleh; I., Waini; S., Shafie (Centre for Advanced Research on Energy (CARe), 2017)
This article presents the mixed convection boundary layer flow over a circular cylinder placed in a viscoelastic micropolar fluid with surface heat flux. The goveming boundary layer equations are transformed into non-dimensional form by using appropriate dimensionless variables Then, the resulting equattons are transformed into similarity equations and solved using an implicit finite difference scheme known as the Keller box method. For validation purpose, the current results are compared to previous study. With congruent results from both study. authors are convinced that the proposed model is reliable.